Melatonin pretreatment does not modify extrasystolic burden in the rat ischemia-reperfusion model - Durkina, A V; Bernikova, O G; Mikhaleva, N J; Paderin, N M; Sedova, K A; Gonotkov, M A; Kuzmin, V S; Azarov, J E (Journal of physiology and pharmacology, 2021)
The mechanism of reentrant ventricular tachyarrhythmias complicating acute myocardial ischemia is largely based on the interaction between an arrhythmogenic substrate and triggers. Melatonin was proposed as an antiarrhythmic medication and was shown to ameliorate the arrhythmogenic substrate. Also, melatonin provides a sympatholytic effect in different settings and might attenuate ectopic activity, which provides reentry triggers. In the present study, we aimed at evaluating the melatonin effects on cardiac sympathetic activity and the incidence of premature ventricular beats during the episode of ischemia-reperfusion. Experiments were done in a total of 26 control and 28 melatonin-treated (10 mg/kg, daily, for 7 days) male rats. Sympathetic fibers density was assessed by glyoxylic acid-induced fluorescence. Continuous electrocardiograms recording was performed during ischemia-reperfusion episodes (5 min/5 min, respectively) induced by reversible coronary occlusion. Myocardial expression of tyrosine hydroxylase, a rate-limiting enzyme of catecholamine biosynthesis was assessed by Western blotting. No differences in the state of sympathetic innervation were observed in histochemical analysis. However, Western blotting analysis demonstrated that melatonin treatment suppressed tyrosine hydroxylase expression in the non-ischemic (p < 0.05 versus control) but not ischemic regions of myocardium. The melatonin-treated animals had longer RR-intervals in the baseline state than the control animals (264 ± 48 ms versus 237 ± 33 ms, p = 0.044, respectively), but this difference decayed during the period of ischemia due to the increase of heart rate in the treated group. The number of premature ventricular beats did not differ between the control and treated groups during the ischemic and reperfusion periods. One-week melatonin pretreatment caused a slight peripheral sympatholytic effect that attenuated during ischemia and completely disappeared by the onset of reperfusion. The slight expression of sympathetic downregulation was associated with the lack of any effect of melatonin on extrasystolic burden. Collectively, the data suggest that melatonin cannot target the triggers of reentrant arrhythmias.
Keywords: antiarytmika; Tachycardia, Ventricular; elektrokardiografie; Rats; Disease Models, Animal; Rats, Wistar; mužské pohlaví; Myocardial Reperfusion Injury; Myocardial Ischemia; Heart Rate; krysa rodu Rattus; srdeční frekvence; reperfuzní poškození myokardu; Electrocardiography; modely nemocí na zvířatech; zvířata; Melatonin; melatonin; komorová tachykardie; ischemická choroba srdeční; potkani Wistar; Anti-Arrhythmia Agents; Male; Animals